Do Markets Value Advanced Service Development? - Korkeamäki, Lauri; Kohtamäki, Marko; Ranta, Mikko (Aston Business School, 2022)
Purpose: Markets have a proven propensity for valuing research and development (R&D) intensity of manufacturing firms. This paper investigates whether coupling R&D intensity with advanced services (ADS) yields even higher market performance effect. Design/Methodology/Approach: The longitudinal financial and annual report data covered a period from 1994 to 2020 (n = 164, N = 2 844). Panel regression (fixed effects estimator) was used to investigate the relationships between market performance (regressand), R&D intensity (regressor) and annual report-level discourse related to ADS (moderator). Findings: The findings confirm that markets do in fact value R&D intensity of manufacturers more if the manufacturer publicizes ADS. However, in alignment with extant research the direct relationship between market performance and ADS discourse proved to be negative and significant. Originality/Value: The current study shows that ADS publicizing adds to the R&D-driven market value of manufacturing firms. Thus, the study contributes to the literature on financial consequences of servitization. However, it also highlights the challenging nature of ADS strategies.
Keywords: Advanced services (ADS); Digital servitization; Financial consequences of servitization; Market performance; Research and development (R&D); service innovation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Strateginen johtaminen|en=Strategic Management|